The Grammatical and Syntactic Preferences of Al-Shatiby in “Al-Maqasid Al-Shafeyah”: Collection and Studying - Al-Samrrai, Mohammed (Al-Adab Journal, 2024)
The alfiat Ibn Maalik in syntax is considered on of the most famous grammatical systems. It had many explanations such as "Al-Bahjah Al-Murdiyah" for Al-Suyuti, and "Sharh Ibn Aqil" and "Awdah Al-Masalik" and "Sharh al-Ashmooni. The widest of them" Al-Maqasid Al-Shafeya" by Abu Ishaq Al-Shatibi. The topic of this research is (the grammatical and syntactic preferences of Al-Shatiby in his book “al-Maqasid al-Shafeyah” – collection and studying). It sheds light on the preferences of al-Shatiby in the book and studies and analyzes them. I began my research with a brief introduction of al-Shatiby and his book. Then I made my study based on four topics. The first one is a general overview of the preferences of al- Shatiby; while the second shows the preferences based on the fundamentals of syntax and grammar. In the third topic I highlight preferences based on the meaning and consideration of the equivalent words with parallel meaning. Lastly, the fourth compares the preferences in the al-Alfeyah to the book (Tasheel al-Fawaid) by Ibn Malik. Through this research, I have reached several conclusions. Firstly, Al-Shatiby mostly mentions the more accurate opinion after simplifying all other opinions about it. He may even just mention the preference without bringing up the opinions, reasons, or evidence on the issue. Secondly, Al-Shatiby is more inclined to give preference to the opinion of Ibn Malik, and the Basrians, and to what is in al-Alfeyah than what is in (Tasheel al-Fawaid). Thirdly, there are preferences based on the fundamentals of syntax and grammar, and preferences based on other factors such as meaning and consideration of the equivalent words with parallel or similar meanings.